(untitled) (Journal of Scientific Research, 2024)
This research focuses on synthesizing aromatic or heteroaromatic compounds with potential pharmaceutical and medicinal applications. Imidazole derivatives have garnered significant attention due to their versatile therapeutic potential, encompassing a broad spectrum of diseases, including cancer, bacterial infections, fungal infections, and malaria. To accomplish this, we have developed an efficient synthetic route to explore a diverse array of 2-((1,4-diphenyl-1H-imidazol-2-yl)thio)-N-(4-(3-oxomorpholino)phenyl) acetamide derivatives. The structural elucidation of the synthesized compounds was carried out using advanced techniques, including 1H and 13C NMR, FT-IR spectroscopy, mass spectroscopy, and elemental analysis. Furthermore, the oxo morpholino-imidazole derivatives synthesized in this study were further employed to produce diverse chemotherapeutic agents with significant potential for clinical applications.